1988
DOI: 10.1038/clpt.1988.215
|View full text |Cite
|
Sign up to set email alerts
|

Sore throat pain in the evaluation of mild analgesics

Abstract: A double-blind, single-dose parallel study was conducted to assess refinements of a previously tested model for evaluating treatment of sore throat pain. Patients with tonsillopharyngitis randomly received either 400 mg ibuprofen (n = 39), 1000 mg acetaminophen (n = 40), or placebo (n = 41). At hourly intervals for 6 hours the patients reported pain intensity and pain relief on conventional scales and two sensory qualities of throat pain ("swollen throat" and "difficulty swallowing") on two new visual analog s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 0 publications
2
79
0
Order By: Relevance
“…accepted and validated Sore Throat Pain Model methodology, [13][14][15][16][17][18][19][20] which has also been employed in previous studies of flurbiprofencontaining sore-throat lozenges. [8][9][10] Statistical analysis All raw data were listed and sorted by patient randomisation number (including patient initials) and visit/assessment (that is, time point), where applicable.…”
Section: How This Fits Inmentioning
confidence: 99%
“…accepted and validated Sore Throat Pain Model methodology, [13][14][15][16][17][18][19][20] which has also been employed in previous studies of flurbiprofencontaining sore-throat lozenges. [8][9][10] Statistical analysis All raw data were listed and sorted by patient randomisation number (including patient initials) and visit/assessment (that is, time point), where applicable.…”
Section: How This Fits Inmentioning
confidence: 99%
“…Two trials comparing guaifenesin with placebo have been conducted; one showed a reduction in coughing with guaifenesin, while the other did not (18). Acetaminophen reduces pharyngeal soreness and headaches (19,20). Carbinoxamine maleate exhibits an antihistaminic effect against nasal symptoms (21).…”
Section: Discussionmentioning
confidence: 99%
“…53 The DERP reviews are updated at least annually, and are subject to peer review and public comment before final publication. 54 These sources were sufficient for evaluating most claims, but for six claims, the coders were provided with additional references: publications from head-to-head trials comparing acetaminophen to ibuprofen, [55][56][57][58][59][60][61] IMS Health data from 2008 to evaluate a claim of prescription popularity, 62 nonprescription label information for a discontinued product from an archived web page, 63,64 links to specific nonprescription drug product labels to evaluate the incipient ingredients in the product, 65,66 and a press release providing up-to-date information to support an advertising claim. 67 We only used publicly available evidence to evaluate claims and did not make requests to pharmaceutical companies for unpublished or "on-file" evidence.…”
Section: Coding: Evaluating the Truthfulness Of The Major Claimmentioning
confidence: 99%